A comparative study on the takeoff and early flight phases in ski junping - Song, J. H.; Moon, Y. J.; Kwon, Y. H. (International Journal of Applied Sports Sciences, 2004)
The purposes of this study were to perform a comparative analysis of the takeoff and early-flight posture variables of the trials performed by three Korean national ski jumpers and to provide an in-depth performance analysis. Three video cameras were used in recording the 90-m jump trials and the 2-dimensional DLT method was used for the camera calibration. Postural angle variables were computed from two sagittal views and one frontal view. Jumpers revealed very different jumping strategies. Jumper A was characterized by a strategy relying on the leg (knee and hip) extension predominantly. Subject B revealed a strategy using an accessory trunk motion. Subject C produced a countermovement takeoff using the arms. Subjects A and B produced more upward jumps than subject C, showing similar plate attitude angle patterns. Subject C was characterized by a more horizontal jump, resulting in a flatter plate attitude and delayed transition to the flat V position. Subject B showed a much lower trunk position than others during the takeoff and early flight phases. Subject C demonstrated a quick transition into the forward leaning flight position during the early flight phase in spite of the relative more posterior body CM position during the in-run and takeoff phases. All subjects gradually increased the plate V angle to reach the flat V style between 0.05 to 0.1 s after the takeoff. ABSTRACT FROM AUTHOR This paper is translated from outstanding Korean paper of "Korean Journal of Sport Science (2003, Vol. 14. No. 3. 75-85)